Electric field of the undisturbed atmosphere in Tomsk - Pustovalov, Konstantin N.; Nagorskiy, Petr M.; Oglezneva, Maria V.; Smirnov, Sergey V. (Proceedings of SPIE)
In the study, estimates of the variability of the surface electric field in undisturbed atmospheric conditions in Tomsk were obtained. It is noted, that the average and mode of the potential gradient in Tomsk under fair-weather conditions are ~280 and 250 V/m, and it is a typical range is 160–370 V/m. In the warm period of the year, the average and range of the potential gradient are 1.2 and 1.5 times, which less than in the cold period.